2017
DOI: 10.3389/fpls.2017.00413
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNAs in Kiwifruit and Their Species-Specific Response to Bacterial Canker Pathogen Invasion

Abstract: Research studies have recently focused on circle RNAs (circRNAs) in relation to their regulatory functions in animals. However, the systematic identification of circRNAs in plants, especially non-model plants, is limited. In addition, raw report on the prediction of the potential role of circRNAs in plant response to pathogen invasion is currently available. We conducted the systematic identification of circRNAs from four materials originating from three species belonging to genus Actinidia under different sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 41 publications
(79 reference statements)
6
76
0
1
Order By: Relevance
“…Past researches revealed that most circRNAs may regulated the expression level of their corresponding host genes in many species [22,29,33]. For example, circMbl can act as a competitor for linear mRNA to regulate gene function [25].…”
Section: Disscusionmentioning
confidence: 99%
“…Past researches revealed that most circRNAs may regulated the expression level of their corresponding host genes in many species [22,29,33]. For example, circMbl can act as a competitor for linear mRNA to regulate gene function [25].…”
Section: Disscusionmentioning
confidence: 99%
“…circRNAs regulate gene expression in animals through different mechanisms, such as miRNA sponges, specific RNA-RNA interactions, and affecting alternative splicing . Since the identification of their roles in regulating gene expression in animals (Memczak et al, 2013), circRNAs have also been identified in different plant species, including Arabidopsis (Arabidopsis thaliana), rice, wheat (Triticum aestivum), barley (Hordeum vulgare), maize (Zea mays), tomato (Solanum lycopersicum), potato (Solanum tuberosum), soybean (Glycine max), cotton (Gossypium hirsutum), and kiwifruit (Actinidia deliciosa; Wang et al, 2014Wang et al, , 2017bWang et al, , 2017cLu et al, 2015;Ye et al, 2015Ye et al, , 2017Darbani et al, 2016;Zuo et al, 2016;Chen et al, 2017Chen et al, , 2018Zhao et al, 2017).…”
mentioning
confidence: 99%
“…Recently, with the development of high-throughput sequencing technology, increasing numbers of circRNAs have been detected in plants and animals. In plants, circRNAs are closely related to plant development and stress responses, including biotic and abiotic stresses [20,[22][23][24][25][26][27][28]30,53]. However, whether circRNAs participate in the pathways of plant responses to hormones is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Plant circRNAs are as conserved and tissue specific as animal circRNAs, but their flanking introns do not contain as many repetitive elements and reverse complementary sequences as those in animals [15,16,19,29]. Recent studies have suggested that plant circRNAs play functional roles in developmental processes and stress responses, including the responses to drought, chilling injury, nutrient deficiency, and pathogen invasion [19,20,22,24,25,30]. Based on the functions of animal circRNAs, circRNA-miRNA-mRNA networks have been generated for plants; these networks suggest that plant circRNAs may act as miRNA sponges to regulate functional gene expression [23,25,31].…”
Section: Introductionmentioning
confidence: 99%